HEALTH LITERACY AND FACTORS RELATED TO DENGUE HEMORRHAGIC FEVER PREVENTION AND CONTROL BEHAVIOR IN VILLAGE HEALTH VOLUNTEERS IN MUEANG KHON KAEN DISTRCT KHON KAEN PROVINCE - เบญจมาศ จินทภา; หีบแก้ว ปัดชาสุวรรณ์ นาฏนภา; อุทธาโพธิ์ พวงผกา (Primary Health Care Journal (Northeastern Edition), 2025)
Dengue fever is a mosquito-borne viral disease, particularly prevalent during the rainy season, which promotes mosquito breeding. Strengthening the health literacy of village health volunteers (VHVs) is crucial for sustainable community-based prevention and control. This cross-sectional analytical study aimed to assess the level of health literacy and its associated factors related to dengue prevention and control behaviors among VHVs. A total of 108 VHVs from Mueang Khon Kaen District, Khon Kaen Province participated. Data were collected using a structured questionnaire and analyzed using simple logistic regression. Results were reported as crude odds ratios (COR), 95% confidence intervals (CI), and p-values at a significance level of 0.05. The findings revealed that 81.48% of participants had low to moderate levels of health literacy, while 82.41% demonstrated good prevention and control behaviors. Significant factors associated with these behaviors included access to information (COR = 4.32; 95% CI: 1.42–13.05; p = 0.010), self-management skills (COR = 3.67; 95% CI: 1.27–10.59; p = 0.016), media literacy (COR = 4.19; 95% CI: 1.29–13.64; p = 0.017), and decision-making skills (AOR = 10.14; 95% CI: 2.26–47.77; p = 0.003). In conclusion, improving health literacy, particularly in accessing information, self-management, media literacy, and decision-making-can enhance VHVs’ ability to engage in effective dengue prevention and control. Targeted training and communication strategies are recommended to promote sustainable behavior change.